Innovative and Sustainable Financial Management in Tahfiz Schools: Strategies for Independence, Efficiency, and Transparency - Pahlawan, Ryan (Journal of Posthumanism, 2025)
Tahfiz schools play a vital role in nurturing spiritually grounded and ethically aware generations within Muslim societies. However, many of these institutions face significant financial sustainability challenges due to their heavy reliance on unpredictable external funding. This study explores innovative strategies to enhance financial independence and transparency in tahfiz schools. Using a descriptive qualitative methodology through comprehensive library research, the paper identifies key approaches, including funding diversification, digital financial integration, and the implementation of Sharia-compliant investment mechanisms. Findings indicate that establishing income-generating units—such as cooperatives and halal-based enterprises—can provide consistent revenue streams. Moreover, adopting financial technology and transparent reporting systems fosters stakeholder trust and improves operational efficiency. The study concludes that aligning financial practices with Islamic ethical principles and contemporary tools can significantly strengthen institutional sustainability. Practical implications include the need for capacity building in entrepreneurial and Sharia-compliant financial literacy for school administrators, fostering partnerships with Islamic financial institutions, and implementing real-time donor transparency dashboards. These strategies provide actionable solutions for tahfiz schools to achieve long-term financial resilience while preserving their religious mission.